From relativism in physics education to objectivism in physics - Marcos Rodrigues da Silva; Carlos Eduardo Laburu (Investigações em Ensino de Ciências, 2000)
In this paper, we shall analyse the contrast between constructivism in the physics teaching and methodological objetictivism about physics. We will show that many pedagogical, epistemological and ontological constructivist perspectives are at the core of criticism of science education literature. We will also show, particularly, that the epistemological and ontological criticism is supported by eminent physicists. Our main concern will concentrate on relativist statute aspect of constructivism, that transfer epistemic and ontological presuppositions of learning-teaching process, to an understanding of the nature of development of the scientific knowledge. Finally, we will try to see in what manner it is not necessary to compromise with a realistic epistemology in order to make the objectivist posture defensible in physics.